Effects of different doses of remimazolam on the quality of sedation and cardiac function in elderly patients: a double-blind randomised controlled study - Minghong, Liu; Feng, Qizhu; Chen, Huichun; Li, Ju; Shi, Jun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundWe intended to observe the effects of different doses of remimazolam besylate via intravenous induction on the quality of sedation and cardiac function in elderly patients.MethodsA total of 135 ASA I–III patients undergoing elective laparoscopic cholecystectomy were selected. They were divided into three groups and they were randomized. Low dose group (Group L): Remimazolam besylate 0.2 mg/kg; middle dose group (Group M): Remimazolam besylate 0.3 mg/kg; High dose group (Group H): Remimazolam besylate 0.4 mg/kg. There were 45 patients in each group. The blood pressure, heart rate, BIS values, cardiac function before induction (T0), after induction (T1) and after intubation (T2), as well as the length of loss of consciousness, duration of sedation, and extubation and adverse events were recorded.ResultsAt T1 and T2, systolic and diastolic blood pressure in Group M were lower than those in Group L, but higher than those in Group H, with statistically significant differences (P < 0.05). At T1 and T2, the BIS value in Group M was lower than that in Group L, with a statistically significant difference (P < 0.05). However, there was no statistically significant difference (P > 0.05) in BIS values between Group M and Group H; At T1 and T2, the cardiac output and stroke volume in Group M were higher than those in Group H, while the systemic vascular resistance in Group M was lower than that in Group H, with statistically significant differences (P < 0.05); The incidences of bucking when moving and hiccup in Group L were higher than those in Group M and Group H, with statistically significant differences (P < 0.05). The number of vasoactive drugs used in Group H was higher than that in Group L and Group M, with statistically significant differences (P < 0.05).ConclusionsGeneral anesthesia induction with remimazolam besylate at 0.3 mg/kg in elderly patients undergoing laparoscopic cholecystectomy showed good quality of sedation, could achieve rapid intubation, with minimal effect on cardiac function and generally favorable safety profile.